Board Independence, Audit Committee Characteristics, and Sharia Supervisory Board on Audit Report Lag - Julfa, Siti; Wafiroh, Novi Lailiyul (E-Jurnal Akuntansi; Vol 34 No 12 (2024), 2024)
This study empirically examines the influence of board independence, audit committee size, audit committee expertise, audit committee meeting frequency, and the presence of Sharia Supervisory Boards (SSBs) on audit report lag. The research focuses on Islamic banking entities, specifically Islamic Commercial Banks (BUS) and Sharia Business Units (UUS) listed with the Financial Services Authority (OJK) in Indonesia during the 2019–2023 period. The sample was determined using a purposive sampling technique, resulting in 130 observations that met the specified research criteria. Data analysis was conducted using logistic regression to assess the relationship between the governance variables and audit report lag. The findings indicate that board independence, the frequency of audit committee meetings, and the presence of an SSB have a significant negative effect on audit report lag, suggesting these factors contribute to faster audit completion. In contrast, audit committee size and audit committee expertise do not exhibit a statistically significant effect. This study introduces a novel perspective by incorporating SSB variables and adapting the measurement approach to reflect the Indonesia Stock Exchange (IDX) policy, which extends the deadline for financial report submissions. The results provide valuable insights into the governance mechanisms that can potentially enhance audit efficiency and reduce audit report lag within the context of Islamic banking.